Deep-Ultraviolet Emitting AlGaN Multiple Quantum Well Graded-Index Separate-Confinement Heterostructures Grown by MBE on SiC Substrates - Haiding Sun; Jian Yin; Emanuele Francesco Pecora; Luca Dal Negro; Roberto Paiella; Theodore D. Moustakas (IEEE Photonics Journal, 2017)
Deep-ultraviolet emitting structures based on Al0.65Ga0.35N/Al0.8Ga0.2 N multiple quantum wells (MQWs), embedded in compositionally graded AlxGa 1−xN films in the form of graded-index-separate-confinement heterostructure, were grown by molecular beam epitaxy. The graded AlGaN layer blocked threading defects (TDs) in the vicinity of the AlN/AlGaN heterointerface, resulting in a reduction of the TDs in the active layer. The intensity of the transverse-magnetic polarized amplified spontaneous emission spectra with peak emission at 270 nm was found to increase linearly with the number of QWs. Furthermore, while the peak intensity for devices with a single QW varies linearly with the pump fluence, it varies superlinearly for larger number of QWs, suggesting light amplification by stimulated emission. These results are consistent with numerical simulations, which indicate that the confinement of the optical mode in this device structure increases with the number of QWs and simultaneously the threshold under optical pumping decreases with increasing of the number of QWs. Finally, the band structure simulations indicate that the device is in the form of a p-n junction due to polarization-induced p- and n-doping in the compositionally graded AlxGa1-xN films on either side of the MQWs, and, thus, could be used for the development of an electrically pumped deep-ultraviolet laser by further optimizing the structures.